Involvement of ethylene receptors in the salt tolerance response of Cucurbita pepo. (1st April 2021) - Cebrián, Gustavo; Iglesias-Moya, Jessica; García, Alicia; Martínez, Javier; Romero, Jonathan; Regalado, José Javier; Martínez, Cecilia; Valenzuela, Juan Luis; Jamilena, Manuel
Abstract: Abiotic stresses have a negative effect on crop production, affecting both vegetative and reproductive development. Ethylene plays a relevant role in plant response to environmental stresses, but the specific contribution of ethylene biosynthesis and signalling components in the salt stress response differs between Arabidopsis and rice, the two most studied model plants. In this paper, we study the effect of three gain-of-function mutations affecting the ethylene receptors CpETR1B, CpETR1A, and CpETR2B of Cucurbita pepo on salt stress response during germination, seedling establishment, and subsequent vegetative growth of plants. The mutations all reduced ethylene sensitivity, but enhanced salt tolerance, during both germination and vegetative growth, demonstrating that the three ethylene receptors play a positive role in salt tolerance. Under salt stress, etr1b, etr1a, and etr2b germinate earlier than WT, and the root and shoot growth rates of both seedlings and plants were less affected in mutant than in WT. The enhanced salt tolerance response of the etr2b plants was associated with a reduced accumulation of Na + in shoots and leaves, as well as with a higher accumulation of compatible solutes, including proline and total carbohydrates, and antioxidant compounds, such as anthocyanin. Many membrane monovalent cation transporters, including Na + /H + and K + /H + exchangers (NHXs), K + efflux antiporters (KEAs), high-affinity K + transporters (HKTs), and K + uptake transporters (KUPs) were also highly upregulated by salt in etr2b in comparison with WT. In aggregate, these data indicate that the enhanced salt tolerance of the mutant is led by the induction of genes that exclude Na + in photosynthetic organs, while maintaining K + /Na + homoeostasis and osmotic adjustment. If the salt response of etr mutants occurs via the ethylene signalling pathway, our data show that ethylene is a negative regulator of salt tolerance during germination and vegetative growth. Nevertheless, the higher upregulation of genes involved in Ca 2+ signalling ( CpCRCK2A and CpCRCK2B ) and ABA biosynthesis ( CpNCED3A and CpNCED3B ) in etr2b leaves under salt stress likely indicates that the function of ethylene receptors in salt stress response in C. pepo can be mediated by Ca 2+ and ABA signalling pathways.